Development of Komat (Math Comics) Based on Problem Based Learning on SPLDV Material - Aldi, Aldi (EDUCTUM: Journal Research, 2023)
This research aims to produce valid and effective problem-based learning KOMAT (Math Comics) learning media products. This research is a type of development research and uses ADDIE model research procedures, namely the analysis stage, the design stage (Design), development stage (Development), implementation stage (Implementation) and evaluation stage (Evaluation). The results of this research: 1) researchers have produced KOMAT Learning Media (Math Comics) based on Problem Based Learning; 2) the results of the assessment of KOMAT Learning Media (Math Comics) from material experts with a percentage score of 97% in the very valid category, and the assessment of KOMAT Learning Media (Mathematics Comics) from media experts with a percentage of 94% in the very valid category; 3) trial results in class VIII-G via pretest before using KOMAT Learning Media (Mathematical Comics) with an average percentage of 59%, trial results in class VIII-G via posttest after using KOMAT Learning Media (Mathematical Comics) with an average percentage of 88% in the complete category; 4) the results of the assessment trial in class VIII-G through a student response questionnaire with an average percentage of 88% in the very effective category. From the results of the assessment by material experts, media experts, student posttest results, and student responses, the KOMAT Learning Media (Math Comics) developed is valid and effective for use as learning media by participants.